Estimating the Effect of Fractal Dimension on Representative Elementary Volume of Randomly Distributed Rock Fracture Networks. (29th October 2018) - Zhang, Jing; Yu, Liyuan; Jing, Hongwen; Liu, Richeng
Abstract : The effect of fractal dimension (D f ) on the determination of representative elementary volume (REV) was investigated through numerical experimentations, in which a new method was adopted to extract submodels that have different length-width ratios from original discrete facture networks (DFNs). Fluid flow in 1610 DFNs with different geometric characteristics of fractures and length-width ratios was simulated, and the equivalent permeability was calculated. The results show that the average equivalent permeability (K R E V ) at the REV size for DFNs increases with the increase inD f . TheK R E V shows a downward trend with increasing length-width ratio of the submodel. A strong exponent functional relationship is found between the REV size andD f . The REV size decreases with increasingD f . With the increment of the length-width ratio of submodels, the REV size shows a decreasing trend. The effects of length-width ratio andD f on the REV size can be negligible whenD f ≥ 1.5, but are significant whenD f < 1.5 .